Economic forces and Islamic stock market: Empirical evidences from Malaysia - Mustafa, Siti Aisyah; Ramlee, Roslily; Kassim, Salina (Faculty of Business and Accountancy, University of Malaya, 2017)
Manuscript type: Research paper Research aims: This study aims to investigate the impact of macroeconomic forces on the Malaysian Islamic stock market. Design/ Methodology/ Approach: The study employs Auto Regressive Distributed Lag (ARDL) bound testing approach and Vector Error Correction Model (VECM) in an attempt to investigate the impact of macroeconomic forces on the Malaysian Islamic stock market. Various domestic economic factors including money supply, industrial activities, inflation, Islamic interbank rate and international issues (e.g., real effective exchange rate and Federal funds rate), are taken into consideration in the analysis. Research findings: Based on the ARDL approach, this study finds that all macroeconomic factors, with the exception of Islamic interbank rate are significantly related to Islamic stock price in the long term. However, the findings from VECM method confirm the significant causal flow from all macroeconomic forces into Islamic stock prices in the longer term. Nevertheless, in the short term, only Islamic stock prices have immediate replies in response to the industrial activities, inflation, real effective exchange rate and Federal funds rate data. Theoretical contributions/ Originality: While there is vast literature on the Islamic stock market, the effect of macroeconomic forces on the Islamic stock price has not been well-researched. This study fills in the gap by investigating the relationship between macroeconomic variables and Islamic stock price. Practitioner/ Policy implications: The findings demonstrate that investors and policymakers should take into account the fluctuations in the macroeconomic variables since they have high information content regarding the future movements of Islamic stock price. The foreign factors, in particular, depict stronger influence on the Islamic stock market than the domestic factors. Research limitations/ Implications: Cheaper currency would accelerate export sector and recovery of the U.S. economy might put Islamic stock market at disadvantage because there is possibility that international investors will switch back their investment.